A Semiotics Analysis of Verbal and Non-Verbal Signs in Drug Posters - dwijaya, andika; Permana, I Putu Andri (British (Jurnal Bahasa dan Sastra Inggris), 2024)
This research aims to analyze verbal and non-verbal signs and explore the meanings of the posters. Posters, which serve as an art of communicating messages, typically consist of short text combined with images, formats, tables, and graphics. Data was collected from Pinterest on the internet, focusing on the signs used in the posters, which are intriguing for analysis. The method employed in this study is qualitative descriptive. Saussure’s (1893) semiotic theory is applied to analyze verbal and non-verbal signs, while Barthes’ (1977) theory of meaning is used to explain the meanings of these signs. The analysis of colors in the posters is conducted using Wierzbicka’s (1996) theory. This research also presents tables and informal methods to describe the meanings of the signs found in the posters. The results indicate that two posters were analyzed, featuring three verbal and four non-verbal signs. These findings highlight the importance of understanding signs in visual communication, particularly in conveying health messages through drug posters. Keywords: semiotics; verbal sign; non-verbal signs; drug posters; meaning analysis